Association of Cataract with Chronic Rhinosinusitis: A Population-based Case-control Study. (December 2014) - Hung, Shih-Han; Ho, Jau-Der; Lin, Herng-Ching; Chung, Shiu-Dong
Abstract Purpose: To assess the association between cataract and chronic rhinosinusitis (CRS) using a population-based database. Methods: The study sample for this case-control study was retrieved from Taiwan's Longitudinal Health Insurance Database 2000. The study included 3045 patients who had undergone cataract surgery as cases and 9135 subjects without cataract as controls. Conditional logistic regression was performed to calculate odds ratios (ORs) and corresponding 95% confidence intervals (CIs) of having a prior diagnosis of CRS in cases versus controls. Results: In the total study sample, the prevalence of prior CRS was 3.88%; 5.16% among cases and 3.45% among controls (p < 0.001). Conditional logistic regression suggested that the unadjusted OR for prior CRS among cases was 1.52 (95% CI 1.25–1.85, p < 0.001) compared to controls. After adjusting for monthly income, residential urbanization and geographic region, the OR for prior CRS among cases was 1.58 (95% CI 1.30–1.94, p < 0.001) compared to controls. Furthermore, the results consistently suggested that cases had higher adjusted ORs for prior CRS than controls across all age groups (40–59, 60–69, and >69 years). It is particularly noteworthy that younger groups demonstrated higher ORs for prior CRS among cases compared to controls. In particular, the adjusted OR for cases aged 40–50 years was 1.71 (95% CI 1.09∼2.66; p < 0.05) compared to controls. Conclusion: While the true relationship between CRS and cataract remains to be further investigated, the result of this present study demonstrated CRS may be associated with cataract.